2009
DOI: 10.1097/psy.0b013e3181b49584
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing in Patients with Noncardiac Chest Pain: Relationships With Pain, Anxiety, and Disability

Abstract: Objective This study examined the contributions of chest pain, anxiety, and pain catastrophizing to disability in 97 patients with non-cardiac chest pain (NCCP). We also tested whether chest pain and anxiety were indirectly related to greater disability via pain catastrophizing. Methods Participants completed daily diaries measuring chest pain for seven days prior to completing measures of pain catastrophizing, trait anxiety, and disability. Linear path model analyses examined the contributions of chest pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 71 publications
0
23
0
1
Order By: Relevance
“…However, several other studies have also involved highly educated samples of NCCP patients (e.g. Aikens et al, 1999;Esler et al, 2003;Shelby et al, 2009). Average age was 50 years (SD = 10.3).…”
Section: Participantsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, several other studies have also involved highly educated samples of NCCP patients (e.g. Aikens et al, 1999;Esler et al, 2003;Shelby et al, 2009). Average age was 50 years (SD = 10.3).…”
Section: Participantsmentioning
confidence: 96%
“…Further, these overemphasized interpretations of pain are associated with physical and psychosocial impairments (Shelby et al, 2009). Other research has found a direct link between perceiving cardiac sensations as uncontrollable and experiencing those sensations as intense and fear provoking (Zvolensky, Feldner, Eifert, Vujanovic, & Solomon, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, a vicious circle may be created if patients catastrophize their pain, which gives rise to pain-related fear and safety seeking behaviour, such as avoidance (16,83). Pain catastrophizing refers to pain being interpreted as extremely threatening (16), and there is a tendency to magnify the pain sensation and feel helpless and unable to inhibit pain-related thoughts (84,85). Pain catastrophizing is associated with both physical and psychosocial disability (84).…”
Section: Fear Of Body Sensations and Fear Avoidancementioning
confidence: 99%
“…Pain catastrophizing refers to pain being interpreted as extremely threatening (16), and there is a tendency to magnify the pain sensation and feel helpless and unable to inhibit pain-related thoughts (84,85). Pain catastrophizing is associated with both physical and psychosocial disability (84).…”
Section: Fear Of Body Sensations and Fear Avoidancementioning
confidence: 99%
“…Chronic pain may negatively affect mood, cognition, and sleep quality of the individuals [13]. Because of the catastrophic thinking, UCP frequently leads to social avoidance, psychosocial problems [10] and may significantly impair the quality of life [14].…”
Section: Introductionmentioning
confidence: 99%